Positive Education for Young Children: Effects of a Positive Psychology Intervention for Preschool Children on Subjective Well Being and Learning Behaviors - Shoshani, Anat; Slone, Michelle (Frontiers in Psychology, 2017)
Despite the flourishing in recent years in applications of positive psychology in the field of education, there is a paucity of research investigating positive psychology interventions for preschool children. The present study examined the effects of a positive psychology-based intervention conducted in Israel on children’s subjective well-being, mental health and learning behaviors. Twelve preschool classrooms of 3–6.5 year-olds were randomly assigned to a positive psychology intervention condition or a wait-list control condition. In the intervention condition, during one school year, 160 children experienced eight modules of basic concepts in positive psychology that were adapted to the developmental characteristics of young children and were compared to 155 children in demographically similar control classrooms. Children were administered a pre-test and post-test of subjective well-being measures. In addition, children’s mental health and emotional well-being were measured by parental questionnaires. Preschool teachers completed questionnaires concerning children’s learning behaviors. The findings showed significant increases in subjective well-being and positive learning behaviors among the intervention participants, with no significant changes in the control group. The results highlight the potential of positive psychology interventions for increasing subjective well-being and a positive approach to learning at young ages.